SIGNIFICANCE OF FINACIAL LITERACY FOR THE AGRICULTURAL HOLDINGS IN SERBIA - Vladimir Zakić; Vlado Kovačević; Jelena Damnjanović (Ekonomika Poljoprivrede (1979), 2017)
The aim of this paper is to analyse the level and the signifcance of farmers financial knowledge or literacy, as well to propose measures for the improvement of financial skills in agricultural holdings. According to the papers results, the level of farmers fnancial knowledge is low; at the state level there hasnt been established satisfying fnancial education of farmers. It is necessary to establish continuous education programs in this feld through agricultural extension services; at the state level, it is important to improve the coordination between different state bodies that conduct an educational program in agricultural sector, as well as the science research results and to make an educational material available to farmers. When considering the signifcance of fnancial literacy, it is usually analyzed from the perspective of adult people. However, recent studies indicate the importance of increasing fnancial literacy already at the level of youth or children. This theoretical concept is currently being accepted in the activities of the Government of the Republic of Serbia. In this regard, the Ministry of Economy has decided to introduce entrepreneurship to primary school through numerous projects.